Sulastri: A biographical study of a woman in the struggle to survive poverty and patriarchal culture - Prasetyo, Hendri Tri; Restuadhi, Hendri; Wuryaningsih, Tri (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
Poverty is a social reality that is difficult to resolve, especially for women. Due to systemic issues and patriarchal social constructions, women are more vulnerable to experiencing poverty. This study explores the connection between poverty and patriarchal norms in deepening the oppression of women, focusing on phenomena such as the double burden, arranged marriages, and early marriages that limit women's well-being. The combination of poverty and patriarchal culture not only exacerbates women's suffering but also profoundly shapes their life experiences. This research adopts a qualitative approach through a biographical study of Sulastri, a woman who lives under the shadow of these issues. Through her biography, key challenges emerge, including: 1) arranged marriages and early marriages that have far-reaching impacts on Sulastri's life; and 2) the double burden of domestic work and economic responsibilities. Despite these conditions, Sulastri demonstrates resilience and determination in overcoming difficulties, significantly impacting her life changes. Sulastri’s story illustrates both individual and collective struggles of women facing interconnected issues. This biographical study provides concrete insights into women’s resilience and their strategies for managing existing limitations. Furthermore, this research emphasizes the need for gender equality initiatives through social programs and policy reforms to address the dual impact of poverty and patriarchal culture.